Optimizacija v proizvodnji - Barle, Janez (Uporabna informatika (Ljubljana), 1995)
There are different computer supported methodologies for production management and planning. In the discrete parts industry MRP (Manufacturing Resources Planning) systems have become the standard planning methodology. In the capital-intensive process industry linear programming and other optimization methods are more typical as approach to planning. Some contemporary planning methods are based on linking od MRP approach with different optimization models. An efficient framework for optimizations models are decision support systems which are usually implemented on personal computers.
Keywords: operacijsko raziskovanje; optimizacija; planiranje; proizvodnja; vodenje